TERMINAL LATENCY INDEX AND RESIDUAL LATENCY IN CAR PAL TUNNEL SYNDROME - Metin Karataş,; Seyhan Sözay,; Meral Bayramoğlu, (Archives of Rheumatology, 2000)
Carpal tunnel syndrome (CTS) has been extensively studied by different electrophysiological techniques for early and accurate diagnosis, but no single measure has adequate diagnostic sensitivity and specificity. Terminal latency index (TLI) and residual latency (RL) are the calculated parameters used to determine abnormality in the distal segment of motor nerve. They adjust the median distal motor latency (MDL) for the terminal distance and the proximal nerve conduction velocity. Three hundred eighty seven hands of 283 patients clinically diagnosed to have CTS were studied. Diagnostic sensitivity of conventional electrophysiological techniques, TLI and RL were analysed compared with each other. While TLI was abnormal in 187 hands (48.3%), MDL was upon normal limits in 145 hands (37.5%). Palmwrist sensory nerve conduction velocity (PLNCV) was the second most sensitive measurement and abnormal in 179 hands (46.3%). Diagnostic sensitivity of TLI was higher significantly from all other measurements, except PLNCV. RL was not superior to conventional electrophysiological techniques. In 13 patients TLI was the only abnormality. In conclusion, TU can be considered as a useful parameter that increases the diagnostic sensitivity in CTS, especially for demonstrating mildly affected motor fibers.